Implicit Intraday Interest Rate in the UK Unsecured Overnight Money Market - Marius Jurgilas; Filip Zikes (Norges Bank, 2013)
This paper estimates the intraday value of money implicit in the UK unsecured overnight money market. Using transactions data on overnight loans advanced through the UK large value payments system CHAPS in 2003-2009, we find a positive and economically significant intraday interest rate. While the implicit intraday interest rate is quite small pre-crisis, it increases more than tenfold during the financial crisis of 2007-2009. The key interpretation is that an increase in implicit intraday interest rate reects the increased opportunity cost of pledging collateral intraday and can be used as an indicator to gauge the stress of the payment system. We obtain qualitatively similar estimates of the intraday interest rate by using quoted intraday bid and offer rates and confirm that our results are not driven by the intraday variation in the bid-ask spread.
hdl:11250/2496700
Keywords: E42; E58; G21; 330; interbank money market; intraday liquidity